Soil salinization in Patagonian meadows with different grassland condition - Cremona, Maria Victoria (2018)
Patagonian meadows (locally named “mallines”) are wetlands that develop in the lower parts of the landscape, were runoff water accumulates, and organic and humid soils appear, contrasting with the surrounding steppe. An internal soil moisture gradient generates different types of vegetation, dominated by Juncus sp in the lower/wetter areas and by Festuca sp. in higher/mesic ones. As meadows have a high primary productivity of forage value, they were heavily grazed mainly by sheep during the last century.